Numerical simulation and experimental investigation of pressure riveting connection using the smoothed particle Galerkin method - Jianhui Zhang; Tongxiang Huang; Xuan Qin; Changcheng Yin; Xianchao Yan (AIP Advances)
This paper conducts experimental and numerical simulations of the riveting process using the Smoothed Particle Galerkin (SPG) method. The riveting process involves significant material failure, making precise simulation challenging. Initially, the mechanical process of riveting and quality testing experiments are briefly described. In addition, the SPG method is introduced. The SPG method is a truly meshless method where nodes are connected through keys, and material failure is simulated by the breakage of these keys. This approach avoids the non-physical responses or erroneous failure modes associated with element deletion methods. Subsequently, three-dimensional finite element models for press-in push-out and press-in twist-out are established to simulate the riveting process and meet the requirements for quality testing of riveted joints. Finally, we compare the force–displacement curves obtained from the simulations and experiments: The maximum riveting force measured in the experiments was 18.5 kN, while the simulated value was 17.8 kN, which is 3.78% lower than the experimental value. The maximum push-out force measured in the experiments was 3.2 kN, and the simulated value was 3.39 kN, which is 5.9% higher than the experimental value. The maximum applied torque measured in the experiments was 24.875 N m, while the simulated value was 24.12 N m, which is 3.03% lower than the experimental value. These comparisons validate the accuracy and limitations of the numerical method. Pressure-riveting connections are extensively used in the high-voltage distribution boxes of electric vehicles, and the quality of these connections is crucial for ensuring vehicle safety. Parameters such as the diameter and thickness of the components being connected can significantly affect the quality of the pressure-riveting connection. Accurate simulation of this process can aid in better understanding of the material behavior during riveting and in designing assembly process parameters.